Importance of early debridement and sterilization in burn: Inspection of infections observed in our burn unit - Akelma, Hakan; Ayhan Karahan, Zeki; Arac, Songul (Annals of Medical Research, 2021)
Aim: In this study, we aimed to investigate the infections that developed in our burn-unit between 2014-2018 and to retrospectively evaluate the patients who have developed in all wound cultures.Materials and Methods: The files of the patients who received inpatient treatment between 2014 and 2018 were evaluated at the Burn Treatment Unit. Nineteen patients who were reproductive in their culture were included in the study. Patients whose files could not be accessed or no records were excluded from the study.Results: The mean age of 19 patients with recorded reproduction by our infection control committee was 15.16 ± 14.63 years and 63.2% were male. All 19 patients have had reproduction. The most common causative agent was Staphylococcus aureus. Reproduction was not detected in any of the blood cultures. When we examined the burn scores of the patients 3 (15.8%) patients had first degree burn, 13 (68.4%) patients had second degree burn, and 3 (15.8%) patients had third degree burn. When we examined the types of Burns, 2 patients had electrical burns (10.5%), 16 patients had hot water burns (84.2%) and 1 patient had hot oil burns (5.3%)Conclusion: As a result of our study, we found the rate of infection, especially the wound infections, in our burn unit to be lower in other (blood, urine and catheter) infections. We consider early surgical excision of patients hospitalized in our department and extreme sensitivity to environmental sterilization and environmental cleanliness of our department may be the cause.
Keywords: Burn; infection; reproduction type